What scholars and IRBs talk when they talk about the Belmont principles in crowd work‐based research. (12th November 2022) - Xia, Huichuan
Abstract: How scholars and IRBs perceive and apply the Belmont principles in crowd work‐based research was an open and largely neglected question. As crowd work becomes increasingly popular for scholars to implement research and collect data, such negligence, signaling a lack of attention to the ethical issues in crowd work‐based research more broadly, seemed alarming. To fill this gap, we conducted a qualitative study with 32 scholars and IRB directors/analysts in the United States to inquire into their perceptions and applications of the Belmont principles in crowd work‐based research. We found two dilemmas in applying the Belmont principles in crowd work‐based research, namely the dilemma between the dehumanization and expected autonomy of crowd workers, and the dilemma between the monetary incentive/reputationall risks and the conventional notion of research benefits/risks. We also compared the scholars' and IRBs' ethical perspectives and proposed our research implications for future work.